Urgensi Perlindungan Konsumen Dalam Perspektif Hukum Dan Islam - Fatmawati Fatmawati; Romi Faslah (CV. ITTC INDONESIA, 2025)
Consumer protection is an important aspect in maintaining a balance between the interests of consumers and business actors, especially in the digital era that is full of new challenges. Strong regulations and strict supervision are needed so that consumer rights are not neglected. However, there are still many consumers who do not understand their rights, making them vulnerable to harmful business practices. In Islam, consumer protection also receives great attention through the principles of honesty, openness, and fairness in transactions. This research uses the literature review method to analyze the implementation of consumer protection, the obstacles faced, and the solutions offered. The results show that there are still many problems in the implementation of consumer protection, especially in digital transactions. The discussion also includes a comparison of international regulations, the importance of consumer education, and the role of supervisory institutions. An Islamic approach is offered as a complement to the modern legal system to realize more comprehensive protection. In conclusion, increasing public awareness, law enforcement, and strengthening the role of supervisors are key to optimizing consumer protection in a sustainable manner.